CLINICAL AND IMMUNOLOGICAL CHARACTERISTICS OF OPPORTUNISTIC INFECTIONS IN CHILDREN WITH HIV INFECTION - V. B. Denisenko; E. N. Simovanyan (LLC "Diagnostics and Vaccines", 2015)
Within 120 months the authors examined 98 children infected with HIV by the parenteral route. During the first years after HIV infection (Me 23-35 months) on the background of a moderate decline in the number of CD4+-lymphocytes (Me 19-20%) localized forms of bacterial infections developed (94,9%), in particular: herpes simplex infection (89,8%) and candidiasis (84,7%). In subsequent years (Me 51-78 months) localized forms of Epstein-Barr viral infection joined (30,6%), pneumocystosis (23,5%), herpes herpes (17,3%), cryptosporidiosis (8,2%) and tuberculosis (5,1%) in conditions of reducing level of CD4+-lymphocytes (Me 9-13%). In the same period (Me 66 months) in 45,9% of patients with a significant decrease in the number of CD4+-lymphocytes (Me 9,5%) generalized forms of opportunistic infections developed.